Conservation of symbiotic signaling since the most recent common ancestor of land plants - Tatiana Vernié; Mélanie Rich; Tifenn Pellen; Eve Teyssier; Vincent Garrigues; Lucie Chauderon; Lauréna Medioni; Fabian van Beveren; Cyril Libourel; Jean Keller; Camille Girou; Corinne Lefort; et al. (Proceedings of the National Academy of Sciences, 2025)
Plants have colonized lands 450 million years ago. This terrestrialization was facilitated by developmental and functional innovations. Recent evo-devo approaches have demonstrated that one of these innovations was the mutualistic arbuscular mycorrhizal symbiosis (AMS). The genetic pathways that have been involved in the establishment and functioning of AMS since its evolution remain poorly described. Here, we found that intracellular colonization by AM fungi induces a transcriptional reporter of the common symbiosis pathway, well-described in angiosperms, in the liverwort Marchantia paleacea . Mutants of either of the three main genes of this pathway, SYMRK , CCaMK, and CYCLOPS, disrupt the ability of M. paleacea to associate with AM fungi. Finally, overexpressing gain-of-function CCaMK or CYCLOPS leads to convergent transcriptomic signatures that partially overlap with AMS. Altogether, our data indicate that plants have maintained three genes of the common symbiotic pathway to support symbiotic interactions since their most recent common ancestor.